2007
DOI: 10.1289/ehp.9685
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Elimination of Inhaled Nanoparticles from the Alveolar Region: Evidence for Interstitial Uptake and Subsequent Reentrainment onto Airways Epithelium

Abstract: BackgroundThere is ongoing discussion that inhaled nanoparticles (NPs, < 100 nm) may translocate from epithelial deposition sites of the lungs to systemic circulation.Objectives and MethodsWe studied the disappearance of NPs from the epithelium by sequential lung retention and clearance and bronchoalveolar lavage (BAL) measurements in healthy adult Wistar Kyoto (WKY) rats at various times over 6 months after administration of a single 60- to 100-min intratracheal inhalation of iridium-192 (192Ir)–radiolabeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
215
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(231 citation statements)
references
References 20 publications
14
215
2
Order By: Relevance
“…The time course of the average MPI value (Figure 4) was very similar to the retention curve of iridium (Ir)-192 nanoparticles with 17-to 20-nm median diameter in the total lung of rats measured using single photon emission computed tomography [14]. Semmler et al [15] reported that Ir-192 nanoparticles were cleared predominantly by mucociliary clearance from the peripheral lung via the airways and larynx into the gastrointestinal tract and were found in feces, and that the fecal excretion observed throughout the entire study of retention during 6 months confirmed the predominance of this clearance pathway.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The time course of the average MPI value (Figure 4) was very similar to the retention curve of iridium (Ir)-192 nanoparticles with 17-to 20-nm median diameter in the total lung of rats measured using single photon emission computed tomography [14]. Semmler et al [15] reported that Ir-192 nanoparticles were cleared predominantly by mucociliary clearance from the peripheral lung via the airways and larynx into the gastrointestinal tract and were found in feces, and that the fecal excretion observed throughout the entire study of retention during 6 months confirmed the predominance of this clearance pathway.…”
Section: Discussionsupporting
confidence: 59%
“…The observation time in these studies, however, is limited by the short half-life of the radioisotopes. In limited cases, clearance of inhaled nanoparticles from the rat lung has been measured over 6 months using radioisotopes with longer half-life such as Ir-192 [14] [15] as mentioned above. Similar studies may be possible using magnetic resonance imaging (MRI) after inhalation of superparamagnetic iron oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings cumulatively support EMT as a potential process by which EPFR-containing PM induces smooth muscle remodeling, a significant component of the asthma phenotype. Studies that have followed the route of PM deposition after inhalation have readily identified particles in the lung interstitial space within the first few hours of exposure (54,55). Therefore, these processes may be occurring very shortly after inhalation, and repeated exposure may contribute to progressive airway remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally known (17) that the nose is efficient at trapping both very large (>5 μm) or very small (<10 nm) particles by inertial impaction and diffusion, respectively, particles of the sizes we used (20 and 80 nm) most likely bypass the upper and central airways and directly enter and deposit deep within the lung. It is important to emphasize that because there is no fast clearance mechanism in the acinus, particles deposited in this region of the lung remain there for extended periods (16,18). Having particles remain in the acinus for extended periods is advantageous for therapeutic drug delivery in a number of ways; for instance, it prolongs the time available for a drug agent to be released, and it increases the chance that the particle crosses the air/blood barrier.…”
mentioning
confidence: 99%